2023
DOI: 10.1007/s10681-023-03159-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and heterotic grouping of quality protein maize (Zea mays L.) inbred lines and derived hybrids under conditions of low soil nitrogen and drought stress

Abstract: Quality Protein Maize (QPM) varieties are rich in lysine and tryptophan, but suffer reduced grain yield (GY) in West and Central Africa (WCA) due to low soil nitrogen (low-N) and intermittent drought stress (DS). Development of stress tolerant QPM hybrids will enhance sustainable maize production and improve nutritional health in WCA. Knowledge of combining ability, gene action and heterotic grouping of QPM inbred lines are crucial to successful breeding strategies for the development of superior hybrids with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
2
0
0
Order By: Relevance
“…The GCA/SCA ratio exceeded one for all traits measured, indicating that additive gene action plays a crucial role in governing the inheritance of these traits. This finding aligns with the research by Owusu et al [67], Ribeiro et al [38], Badu-Apraku et al [68], and Okunlola et al [14], who also observed additive genetic variance to be predominant in the expression of grain yield across different nitrogen levels. However, this stands in contrast to the studies of Betran et al [69], Worku et al [70], and Makinde et al [71], which highlighted the dominance of non-additive gene action in the genetic control of grain yield under similar conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The GCA/SCA ratio exceeded one for all traits measured, indicating that additive gene action plays a crucial role in governing the inheritance of these traits. This finding aligns with the research by Owusu et al [67], Ribeiro et al [38], Badu-Apraku et al [68], and Okunlola et al [14], who also observed additive genetic variance to be predominant in the expression of grain yield across different nitrogen levels. However, this stands in contrast to the studies of Betran et al [69], Worku et al [70], and Makinde et al [71], which highlighted the dominance of non-additive gene action in the genetic control of grain yield under similar conditions.…”
Section: Discussionsupporting
confidence: 91%
“…This suggested that recurrent selection and hybridization can be employed for the genetic improvement of these traits. Similar findings were reported by Wegary et al (2013) and Owusu et al (2023) using the diallel mating method, where both additive and non-additive gene actions were found to be important for the inheritance of grain yield among QPM inbreds under low-N conditions. Meseka et al (2006), Afolabi et al (2019), Abu et al (2021), and Makinde et al (2023) also observed the significance of both additive and non-additive gene actions in the expression of grain yield under low-N conditions.…”
Section: Discussionsupporting
confidence: 87%